Revitalisasi Pariwisata Berbasis Lingkungan: Peran Eco Enzyme dan Kesadaran Masyarakat - Arik Agustina; I Gst Ayu Eka Suwintari; I Gst Ayu Melistyari Dewi (Journal of Innovative and Creativity, 2025)
Environmentally-based tourism is a strategic approach to building economic, social, and ecological sustainability in tourist destinations. This article examines the role of eco-enzymes as an environmentally friendly waste management innovation and increasing public awareness in the revitalization of sustainable tourism. This research method uses a qualitative approach. It began with data and information collection through literature reviews, observations, and discussions with stakeholders. Observations and interviews were conducted with stakeholders in Tegal Harum Village, Denpasar, which is one of the pilot villages related to waste management. This study examines the utilization of organic waste, increasing public education, and the role of the Tegal Harum Village community. The results of this study indicate a synergy between the innovation of organic waste management into eco-enzymes, the role of the community, increasing public awareness, and strengthening community capacity in improving environmental quality and sustainable tourism. This article also recommends the integration of eco-enzymes in regional tourism policies and strengthening community-based education programs as a foundation for sustainable tourism revitalization.